Log in to add a comment

## Answers

Where F directly proportional to rate of change of momentum

F is proportional to (v-u) / t

If we are removing the proportional then there would be a constant added lets assume the constant as K

F=k(v-u/t)

k is constant so k=1

momentum=mv

f=k(-u/t)mv

f=mk(v-u/t) since v-u/t =a

f=kma where k is constant

f=ma

momentum is directly proportional to F

hence dp/dt proportional to F

F=k(dp/dt)

in si unit k=1

F=dp/dt=d(mv)/dt

since m is const.

Hence F=ma